Relationship between DNA damage in liver, heart, spleen and total blood cells and disease pathogenesis of infected rats by Trypanosoma evansi - Baldissera M.D. (2016)
© 2015 Elsevier Inc.Trypanosoma evansi is an important pathogen that causes changes in nitric oxide (NO) levels and antioxidant enzymes, as well as oxidative stress. The present study evaluated the in vivo effect of T. evansi infection on frequency and index of DNA damage in liver, heart, spleen and total blood of rats. Twenty rats were assigned into two groups with ten rats each, being subdivided into four subgroups (A1 and A2, 5 animals/group; and B1 and B2, 5 animals/group). Rats in the subgroups A1 and A2 were used as control (uninfected) and animals in the subgroups B1 and B2 were inoculated with T. evansi (infected). NO in serum and the comet assay were used to measure DNA damage index (DI) and damage frequency (DF) in liver, heart, spleen and total blood of infected rats. Increased NO levels on days 3 and 9 post-infection (PI) was observed (P < 0.001). Also, it was verified an increase on DI and DF in the evaluated organs on days 3 and 9 PI (P < 0.001). Our data show that T. evansi infection causes genotoxicity due to the production of NO, causing not only the death of the protozoan, but also inducing DNA damage in the host.